Clinicopathological and molecular characteristics of extramedullary acute myeloid leukaemia. Issue 2 (20th June 2019) - Ullman, David I; Dorn, David; Jones, Jeffery A; Fasciano, Danielle; Ping, Zheng; Kanakis, Constantine; Koenig, Richard G; Salzman, Donna; Peker, Deniz
Abstract : Aims: Myeloid sarcoma (MS) is a rare extramedullary neoplasm composed of immature myeloid precursor cells thought to be a unique clinical presentation of acute myeloid leukaemia (AML). Like AML, MS has a poor prognosis, but due to the rare nature of MS there are limited studies examining potential prognostic factors. We report our institutional experience, with the aim of investigating and establishing salient clinicopathological and molecular features of MS. Methods and results: We retrospectively examined all clinicopathological and molecular data on MS patients between 2001 and 2017 from the University of Alabama at Birmingham (UAB) electronic medical records. The UAB electronic medical records were also reviewed and compared with the literature for other potential prognostic factors. Sixty‐three patients were included in the study. The median overall survival was 24 months in the group with normal karyotype and 12 months in patients with an abnormal karyotype. Conclusions: We found that an abnormal karyotype was associated with a statistically significant worse prognosis.